2014
DOI: 10.1080/09593330.2014.927928
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for optimization of small-scale RO membrane using artificial groundwater

Abstract: The present study aims at evaluating a small-scale brackish water reverse osmosis (RO) process using parameter optimization. Experiments were carried out using formulated artificial groundwater, and a predictive model was developed by using response surface methodology (RSM) for the optimization of input process parameters of brackish water RO process to simultaneously maximize water recovery and salt rejection while minimizing energy demand. The result of multiple response optimization along with analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…According to Garg et al [26] et salami et al [50] and further confirmation of the permeate recovery prediction of the performance membrane desalination process, the ANN model proposed in this study yielded satisfactory results that can be used as a model for controlling the desalination membrane filtration performance. Since the neural network model shows good accuracy in predicting these parameters, it could be considerate that the ANN the best-simulated model and is suitable for prediction of seawater desalination performance hybrid process NF/RO in the mean of improving the quality of the water produced and reduce water production costs.…”
Section: Comparison Of the Ann Model And Mlr Modelsupporting
confidence: 58%
See 1 more Smart Citation
“…According to Garg et al [26] et salami et al [50] and further confirmation of the permeate recovery prediction of the performance membrane desalination process, the ANN model proposed in this study yielded satisfactory results that can be used as a model for controlling the desalination membrane filtration performance. Since the neural network model shows good accuracy in predicting these parameters, it could be considerate that the ANN the best-simulated model and is suitable for prediction of seawater desalination performance hybrid process NF/RO in the mean of improving the quality of the water produced and reduce water production costs.…”
Section: Comparison Of the Ann Model And Mlr Modelsupporting
confidence: 58%
“…Abbas et al [25] identified the variable of permeate flow rate to be controlled in RO seawater and brackish plant with ANN. Garg et al [26] used ANN simulation to study the performance of small-scale RO membrane which control the permeate recovery, the TDS and specific energy consumption. Aish et al [27] considered the permeate flow rate and TDS adequate variables to control and modeling of five large and small scale brackish water plants in Gaza strip.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the major ions, azo‐based dyes (blue and red dyes) were used in the textile industry for the dying process. Artificial textile wastewater was produced with the help of the inverse matrix method (Adams & Bubucis, 1998; Garg & Joshi, 2014, 2017). Additionally, 30 ppm of methylene blue dye (molecular weight = 319.86 Da, dye content = 70%) acquired from the Central Drug House Pvt., Ltd. (India) was dissolved with the desired quantity of salts obtained through the inverse matrix method in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…where y is the response variable, β 0 is the intercept, β i are the first‐order model coefficients for x i , β ij are the multi‐parameter interaction coefficients for x i x j , β ii are the quadratic coefficients of x i , k is the total number of variables, and ε is the error of the model 25.…”
Section: Methodsmentioning
confidence: 99%